Evaluasi User Experience Dalam Aspek Usability Pada Aplikasi Android Edukasi Literasi Matematika - Rizal Padhilah; Muhammad Raihan Satrio Putra Pamungkas; Syarifah Husniyah; Nisrina Ramadhani Listarto; Annisa Nur Aeni; Rini Marwati (Jurnal KomtekInfo, 2022)
Currently, user experience has becomes an important thing in software development. Few users reportedly has left the application as a result of bad experience that occurs to them. Usability as one of the sub aspect of user experience that play role as a indicator level of how easy user using application is being evaluated in this study. Perceptual difference due to gender and character of children became the choosen topic, so this study aims to determine the significant effect of gender from elementary school students on the results of the usability evaluation that conducted. The application tested in this study is an android-based application called PrismaKu which is present as a smart solution to improve the mathematical literacy skills of elementary school students in Indonesia. This research method refers to previous method named research learning spiral method which is carried out in one cycle. Tests were conducted to measure the duration of each task and application ease of use assessment using the System Usability Scale (SUS). Based on the research results, there are no significant effect of gender from elementary school students on the results of usability neither duration of each task nor system usability scale score. Nevertheless, score and duration show difference as viewed from numerical and descriptive perspective.